A study of online hotel booking towards consumers: consumer’s perception on online hotel booking and its effect on satisfaction / Nur Elliyana Ezzaty Joha - Joha, Nur Elliyana Ezzaty (2018)
The rapid growth of internet application had increased the number of Internet users. Most of the people use internet application to carry out their business includes online hotel booking as the number of user who visit and get through the online hotel booking had increase. Besides, most consumers prefer to go through online hotel booking to make reservations for planning and as their travel products because of many benefits such as many offerings, convenience price comparison and easy for consumers to make choice during purchase. The purpose of this study is to focus on the consumer’s perception on online hotel booking and its effect on satisfaction. There are a few issues on booking reliability and trustworthiness within hotel booking. Most of consumers had to rely fully on the information from the websites since they are not able to “see” or “experience” before purchase that may lead to trust issues. Therefore, this research is made to get know whether the non-deception and privacy in online hotel booking may affects the consumer satisfaction. The questionnaire was developed by Google Form and distributed to the respondents using online survey. The questionnaire was conducted to collect data from respondents. The result from 250 respondents revealed that the hypotheses were supported. There is a positive relationship between each variable.